The Relationship Between the Level of Knowledge of Oral Health and Tooth Loss (Missing) at the age of 17-45 Years (Poltekkes Kemenkes Bandung, 2022)
Knowledge of oral health is something that can affect the quality of a person’s teeth. If someone has good knowledge about dental and oral health, it will have a positive effect on attitudes and actions to maintain dental and oral health, and vice versa. Missing teeth is the removal of a tooth from its socket. Missing teeth at the age of 17-45 years (young adults) is mostly caused by caries. The type of research used is quantitative with analytical methods, by direct examination of respondents to determine the relationship between between the level of knowledge of oral health and the incidence of tooth loss. The number of samples is 36 people. Primary data were obtained from filling out a questionnaire and examining the number of missing teeth from each individual. The results of the chi-square thest using the fisher exact p-value = 0,011 (< 0,05). Conclusion : there is a relationship between the level of knowledge of dental and oral health with the incidence of missing teeth.